Radioprotective effects of flurbiprofen and its nitroderivative - Juchelková, L; Hofer, M; Pospísil, M; Pipalová, I (Physiological research, 1998)
Radioprotective effects of two non-steroidal anti-inflammatory drugs, flurbiprofen (FBP) and its novel nitroderivative flurbiprofen 4-nitroxybutylester (NO-FBP), which exhibits decreased gastrointestinal toxicity, were compared in mice. The drugs were administered in equimolar single doses, 2 hours before whole-body gamma-irradiation of the animals. After a sublethal radiation dose of 6.5 Gy, significantly increased numbers of endogenous haemopoietic spleen colonies and enhanced granulopoiesis were found in mice given either FBP or NO-FBP, when compared to vehicle-treated controls. There were no differences in the effectiveness of either drug to enhance postirradiation haemopoietic recovery. Survival of FBP- or NO-FBP-treated mice subjected to a lethal dose of 9.5 Gy was slightly but insignificantly enhanced, both drugs showing the same effect. These results clearly indicate the ability of both drugs to enhance haemopoietic recovery after sublethal radiation exposure and the absence of unfavourable effects under higher radiation doses. Because of its lower potential for gastrointestinal damage, NO-FBP seems to be a promising drug, which can find a use in the protection of postirradiation myelosuppression.
Keywords: Lymphocyte Count; počet leukocytů; flurbiprofen; analýza přežití; radioprotektivní látky; Radiation-Protective Agents; Leukocyte Count; zvířata; Anti-Inflammatory Agents, Non-Steroidal; myši; antiflogistika nesteroidní; myši inbrední C57BL; Survival Analysis; časové faktory; Mice; Mice, Inbred CBA; granulocyty; Male; Spleen; Mice, Inbred C57BL; počet lymfocytů; Bone Marrow Cells; Flurbiprofen; Animals; myši inbrední CBA; mužské pohlaví; Time Factors; Granulocytes; slezina; buňky kostní dřeně